Changes in mental performance indicators (volume processing visual information) girls junior grades of secondary schools - Prozar, Mykola (Journal of Education, Health and Sport, 2015)
Prozar M. V. Changes in mental performance indicators (volume processing visual information) girls junior grades of secondary schools. Journal of Education, Health and Sport. 2015;5(5):31-43. ISSN 2391-8306. DOI: 10.5281/zenodo.17335 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%285%29%3A31-43 https://pbn.nauka.gov.pl/works/556567 http://dx.doi.org/10.5281/zenodo.17335 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 – 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.02.2015. Revised 27.03.2015. Accepted: 15.04.2015. Changes in mental performance indicators (volume processing visual information) girls junior grades of secondary schools M. V. Prozar Kamenets-Podolsky National University named after Ivan Ohienko, Ukraine Summary. The paper presents results of a study of cognitive function (as one of the components of mental capacity) the amount of visual information processing (AVIP) 40 girls second year of secondary schools in Kamenets-Podolsk №№ 5, 9. To achieve the objectives defined set of methods and means of research. Using methods psychodiagnostic testing identified indicators of mental capacity (volume processing visual information) during the year four times: at the beginning and end of the first and second semesters. The study found that girls’ mental capacity for the second year AVIP characterized by similar figures at the beginning and end of the respective first and second semester of the academic year. The data are characterized by the possibility of keeping mental capacity at the appropriate level without negative health consequences of primary school girls provided to improve the content of their physical education. Key words: mental performance, girl’s second grade, physical education. Prozar Mikołaja, doktor nauk o kulturze fizycznej, docent, Narodowego Uniwersytetu imienia Iwana Ohijenki w Kamieńcu Podolskim, Ukraina. Zmiany wskaźników zdolności umysłowej (ilości przetwarzania informacji wizualnej) uczennic szkoły podstawowej Adnotacja. W artykule przedstawione wyniki badania poziomu kognitywnej funkcji (jak jednej ze składników zdolności umysłowej) ilość przetwarzania informacji wizualnej 40 uczennic drugiego roku szkół ogólnokształcących m. Kamieniec Podolski № № 5, 9. Do rozstrzygnięcia postawionych zadań wyznaczyły kompleks metod i środków badania. Wykorzystawszy metody psychodiagnostycznego testowania, wyznaczyły wskaźniki zdolności umysłowej (ilość przetwarzania informacji wizualnej) w ciągu roku cztery razy: na początku i pod końiec pierwszego i drugiego semestrów. Podczas badania ustalono, że umysłowa zdolność uczennic drugiego roku nauczania za ilością przetwarzania informacji wizualnej charakteryzuje się podobnymi wskaźnikami na początku i w końcu odpowiednio pierwszego i drugiego semestrów roku szkolnego. Otrzymane dane charakteryzują się możliwością utrzymania zdolności umysłowej na odpowiednim poziomie bez negatywnych skutków dla zdrowia uczennic szkoły podstawowej pod warunkiem polepszania treści ich edukacji fizycznej. Słowa kluczowe: zdolność umysłowa, uczennice klasy drugiej, wychowanie fizyczne.